EFEKTIVITAS PEMBELAJARAN GEOGRAFI DENGAN MENGGUNAKAN APLIKASI GOOGLE CLASSROOM DI SMA PEMBANGUNAN LABORATORIUM UNP - PUTRI HASIMAH; Syafri Anwar (JURUSAN GEOGRAFI FIS UNP, 2023)
This study aims to determine the effectiveness of the use of the Google Classroom application in learning Geography and the relationship between the effectiveness of the use of the Google Classroom application on the learning outcomes of Geography students at the UNP Laboratory Development High School. The type of research used is descriptive quantitative research. The subjects in this study were students in grades X, XI and XII in the 2021/2022 academic year. The sampling technique in this study used a cluster random sampling technique, with a total of 77 respondents. Data analysis used a Likert scale using the IBM SPSS 21 program and assisted by Microsoft Excel to process the data. The results of the analysis of the effectiveness of the use of the Google Classroom application in Geography learning by 40.26% are in the